The country of the pointed firs - Jewett, Sarah Orne (New York : Fawcett Publications, 1969)
This edition is for readers for whom English is a second language. It can be anyone whos has learned 2,000 words of english.
Glossary.
Keywords: Novelas; Estados Unidos De America; Literatura Norteamericana